An infinite element algorithm for asymmetric vibration of an embedment in a homogeneous elastic half space - Handunnetti, Sandya; Karasudhi, Pisidhi; Brotton, D.M.; Worsak Kanok-Nukulchai; The Royal Norwegian Government (Bangkok : Asian Institute of Technology, 1986)
An efficient elastodynamic horizontal infinite element capable of propagating Rayleigh waves and body waves in a homogeneous half space is presented. The displacement interpolation functions are presented in convenient explicit forms by formulating the infinite element with respect to a cylindrical coordinate system. The infinite integrals appearing in the impedance matrix of an infinite element are integrated analytically which results in a drastic reduction in computation cost. These horizontal infinite elements and radial infinite elements suggested by Rajapakse are used to model the far field of a homogeneous half space while the near field is modelled by conventional finite elements. The applicability and accuracy of the proposed scheme are confirmed by comparing with rigorous analytical results of lateral and rocking compliances of rigid surface disk and partially embedded rigid cylinder subjected to harmonic loadings.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Elastic analysis (Theory of structures)